THE USE OF YOUTUBE TO SUPPORT EFL STUDENTS' LISTENING SKILLS - Ignasia Yuyun; Fitri Yanti Simamora (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
Authentic material in the English as a Foreign Language (EFL) classroom, particularly in listening, encourages students to apply actual language or authentic speech. In this digital era, Information and Communication Technology (ICT) plays a pivotal role for the teacher's resources to support the teaching-learning process in the classroom. The teacher can find free resources on the Internet by browsing Google, Yahoo, and YouTube. Using YouTube videos can improve students' listening comprehension as it brings many benefits to learners. YouTube is a tool of authentic material to support the student to focus more on listening. The teacher needs to encourage student's motivation in the teaching-learning process. Therefore, this study investigates how YouTube Video is a teaching tool to improve student's listening comprehension skills. There were eight participants from the English Department in a private university in Jakarta. The data was collected through class observation and interviews to observe EFL students' progress in the learning process of listening. This study revealed that YouTube video benefits EFL learners, such as improving students' confidence, enjoying the learning process, making the learning process more fun, and increasing students' interest in learning.